Comparison of Dynamic Measures in Intraoperative Goal-Directed Fluid Therapy of Patients with Morbid Obesity Undergoing Laparoscopic Sleeve Gastrectomy - Urhan, Gokhan; Demirel, Ismail; Deniz, Ahmet; Aksu, Ahmet; Altun, Aysun Yildiz; Bolat, Esef; Altuntas, Gulsum (Springer, 2024)
IntroductionObesity increases the risk of morbidity and mortality during surgical procedures. Goal-directed fluid therapy (GDFT) is a new concept for perioperative fluid management that has been shown to improve patient prognosis. This study aimed to investigate the role of the Pleth Variability Index (PVI), systolic pressure variation (SPV), and pulse pressure variation (PPV) in maintaining tissue perfusion and renal function during GDFT management in patients undergoing laparoscopic sleeve gastrectomy (LSG).Materials and MethodsTwo hundred ten patients were enrolled in our prospective randomized controlled clinical trial. Demographic data, hemodynamic parameters, biochemical parameters, the amount of crystalloid and colloid fluid administered intraoperatively, and the technique of goal-directed fluid management used were recorded. Patients were randomly divided into three groups: PVI (n = 70), PPV (n = 70), and SPV (n = 70), according to the technique of goal-directed fluid management. Postoperative nausea and vomiting, time of return of bowel movement, and hospital stay duration were recorded.ResultsThere was no statistically significant difference between the number of crystalloids administered in all three groups. However, the amount of colloid administered was statistically significantly lower in the SPV group than in the PVI group, and there was no significant difference in the other groups. Statistically, there was no significant difference between the groups in plasma lactate, blood urea, and creatinine levels.ConclusionIn LSG, dynamic measurement techniques such as PVI, SPV, and PPV can be used in patients with morbid obesity without causing intraoperative and postoperative complications. PVI may be preferred over other invasive methods because it is noninvasive.
Keywords: Morbid obesity; Goal-directed fluid therapy; Laparoscopic sleeve gastrectomy; PVI; PPV; SPV; Lactate